Hypothesised and actual changes in the general motor parameters of field hockey players during the training cycle - Strzelczyk, R.; Konarski, J. M.; Karpowicz, K.; Janowski, J.; Bartkowiak, S.; Konarska, A.; Podgórski, T. (Polish Journal of Sport and Tourism, 2018)
Introduction. The aim of the study was to determine the changes in selected motor parameters of highly skilled field hockey players during the training macrocycle. It was assumed that the changes in the parameters examined in the study would correspond with the hypothesised variation related to the adaptive changes that were expected to take place. Material and methods. The study involved eleven field hockey players from the KS AZS-AWF Poznañ club (age = 22.3 ± 1.1 years; height = 176.5 ± 4.0 cm; weight = 75.2 ± 6.3 kg; %FM = 12.2 ± 3.9%; VO2max = 55.4 ± 4.85 ml/kg/min). The dates of the measurements were agreed on with the trainers, who played an active role in the study, and were consistent with the cycle of planned measurements that were aimed at assessing the implementation of training/competition loads (two measurements during the preparatory period and one during the competition period). We examined the fundamental elements of motor preparation that are considered important in field hockey, that is speed endurance, running speed, and aerobic endurance. These assessments were supplemented by the measurements of lactate concentration in capillary blood as well as those of jumping ability and agility. Results. In most cases, the changes in the actual results corresponded with the hypothesised values adopted for the training. The relationships between the levels of particular parameters of the players` motor skills were adequate to a great extent. Conclusion. The effects of the training observed both for the entire team and for individual players were generally in line with the goals of the training/competition loads implemented. Any discrepancies that were found were identified and corrected by regulating individual exercise loads and were monitored in subsequent measurements.